Light‐ and Solvent‐Controlled Self‐Assembly Behavior of Spiropyran–Polyoxometalate–Alkyl Hybrid Molecules. Issue 33 (12th July 2016) - Chu, Yang; Saad, Ali; Yin, Panchao; Wu, Jiayingzi; Oms, Olivier; Dolbecq, Anne; Mialane, Pierre; Liu, Tianbo
Abstract: A molecular photochromic spiropyran–polyoxometalate–alkyl organic–inorganic hybrid has been synthesized and fully characterized. The reversible switching of the hydrophobic spiropyran fragment to the hydrophilic merocyanine one can be easily achieved under light irradiation at different wavelengths. This switch changes the amphiphilic feature of the hybrid, leading to a light‐controlled self‐assembly behavior in solution. It has been shown that the hybrid can reversibly self‐assemble into vesicles in polar solvents and irreversibly into reverse vesicles in non‐polar solvents. The sizes of the vesicles and the reverse vesicles are both tunable by the polarity of the solvent, with the hydrophobic interactions being the main driving force. Abstract : (Reverse)vesicles : The reversible transition between hydrophobic spiropyran and hydrophilic merocyanine isomers in a hybrid photoswitchable polyoxometalate molecule can be achieved under light irradiation. The change of the molecular hydrophobicity leads to the reversible assembly/disassembly of regular vesicles and an irreversible assembly of reverse vesicles in polar and non‐polar solvents, respectively (see figure).